2013
DOI: 10.1111/cdoe.12087
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with dental caries in Brazilian children: a multilevel approach

Abstract: Dental caries experience and severity score of dental caries in primary teeth was influenced by age, household income, and the type of school The dental caries experience in permanent teeth was influenced by age, parents'/caregivers' schooling, household income, and type of school, whereas the severity score of dental caries in permanent teeth was influenced by age and type of school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
4
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 19 publications
5
33
4
4
Order By: Relevance
“…The socioeconomic factor evaluated in the present investigation was per capita household income. Household income is often used as an explanatory variable for dental caries, and the inverse relationship between income and caries is widely recognized . This is the first study to demonstrate that the distribution of untreated dental caries among income strata is partially explained by HFI.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The socioeconomic factor evaluated in the present investigation was per capita household income. Household income is often used as an explanatory variable for dental caries, and the inverse relationship between income and caries is widely recognized . This is the first study to demonstrate that the distribution of untreated dental caries among income strata is partially explained by HFI.…”
Section: Discussionmentioning
confidence: 82%
“…Household income is often used as an explanatory variable for dental caries, and the inverse relationship between income and caries is widely recognized. 18,19 This is the first study to demonstrate that the distribution of untreated dental caries among income strata is partially explained by HFI. Food insecurity is a social health determinant defined as inadequate access to food, which results in a scarcity of food items, irregular eating patterns, and hunger.…”
Section: T a B L E 3 Poisson Model With Robustmentioning
confidence: 91%
“…Those adverse sociodemographic indicators are also related to unfavorable biological characteristics, such as low birth weight and shorter height . Therefore, the relationship between dental caries and the biological factors listed in the present systematic review may exist as a result of the impact of family‐related disadvantages, either social or economic, on developmental patterns and dental health of young individuals along their life course.…”
Section: Discussionmentioning
confidence: 95%
“…The multilevel analysis has been described in the literature as an appropriate statistical approach, allowing estimation of the proportion of the variance at each level [Diez Roux, 2002;Lynch et al, 2004;Celeste and Nadanovsky, 2010a]. Indeed, there are few studies and conflicting evidence about the association of contextual effect on oral health in preschool children Aida et al, 2008;Pereira et al, 2010;Borrell and Baquero, 2011;Borenstein et al, 2013;Martins et al, 2014]. While a study demonstrated a strong influence of contextual factors on dental caries among preschool children [Aida et al, 2008], others showed a weak or no effect, mainly when individual variables were included as controls [Bramlett et al, 2010;Piovesan et al, 2011].…”
mentioning
confidence: 99%